Origin of low carrier mobilities in halide perovskites - Poncé, S; Schlipf, M; Giustino, F (American Chemical Society, 2019)
Halide perovskites constitute a new class of semiconductors that hold promise for low-cost solar cells and optoelectronics. One key property of these materials is the electron mobility, which determines the average electron speed due to a driving electric field. Here we elucidate the atomic-scale mechanisms and theoretical limits of carrier mobilities in halide perovskites by performing a comparative analysis of the archetypal compound CH 3 NH 3 PbI 3 , its inorganic counterpart CsPbI 3 , and a classic semiconductor for light-emitting diodes, wurtzite GaN, using cutting-edge many-body ab initio calculations. We demonstrate that low-energy longitudinal-optical phonons associated with fluctuations of the Pb-I bonds ultimately limit the mobility to 80 cm 2 /(V s) at room temperature. By extending our analysis to a broad class of compounds, we identify a universal scaling law for the carrier mobility in halide perovskites, and we establish the design principles to realize high-mobility materials.